Generic Composition, Structure and Diversity of Secondary Forests at Amisconde, the Pacific Slope of the Cordillera de Talamanca, Costa Rica - Hooftman, D A P (Revista de Biología Tropical, 1998)
Most Costa Rican forests have been intensively studied in recent years. One exception is the transition zone from lowland wet forest to the high elevatíon Quercus forest belt al Ihe pacific slopes of the Cordillera de Talamanca. An inventory of secondary forest composition, structure and diversity was done on a specific slope (l150- 2300-m elevation) in the conservation and development project Amisconde. Thirteen plots of 500 m2 were evenly spread a10ng an elevation gradient. Specimens were collected of a11 woody individuals (> 3 cm DBH), dried, placed in a herbarium of morphospecies and afterwards identified. In total 90 genera within 49 families were found. The vegetation was separated in three forest types using TWINSPAN c1assification. Forest types were elevatíon based. Elevation and forest age showed (overall) no correlatíon with diversity using ANOVA, with the single exceptíon of a positíve correlatíon of the number of genera and elevatíon. This was opposite to the negative correlations mostly found on elevatíon gradients. The main factors for this positíve correlation were the level of recent disturbance and the distance to primary forest, in combination wíth forest age